Sexual dimorphism in cancer - G. A. Belitsky; K. I. Kirsanov; E. A. Lesovaya; V. P. Maksimova; L. V. Krivosheeva; M. G. Yakubovskaya (Успехи молекулярной онкологии)
The incidence and mortality of malignant neoplasms of non-reproductive organs both carcinomas and sarcomas in men is one and a half times higher than in women. This is based on genetic differences, which are superimposed by patterns of epigenetic regulation of the expression of sex chromosome genes that determine sex differences in the processes of tissue differentiation, which, in turn, mediates the formation of the hormonal status of the body. Compared to the Y chromosome, the mammalian X chromosome contains several dozen times more genes encoding major regulators of proliferation, metabolism, immunity, and tumor growth inhibitors, as well as X-linked microRNAs affecting transcription factors and cross-regulation by other non-coding RNAs. This results in a female or male gene expression profile that accounts for phenotypic differences. This peculiarity, along with the fact that in female cells on the second inactivatedX chromosome epigenetic repression of the most important genes is reversed and, accordingly, their expression level is doubled, may largely explain the sex disparity in carcinogenesis. The influence of sex hormones and disparity in the expression of antitumor immunity contribute significantly to this difference. A detailed study of the mechanisms underlying sex dimorphism in carcinogenesis will be an essential contribution to fundamental oncology and to the practice of diagnosis, prognosis and personalized treatment of malignances with regard to their gender-specific course. These studies are especially relevant in relation to insufficiently studied soft tissue sarcomas, the ratio of the frequencies of which in men and women varies greatly depending on the histological subtype of the tumor.